Facies analysis and distribution of Late Palaeogene deep‐water massive sandstones in submarine‐fan lobes, NW Borneo. Issue 11 (8th August 2022) - Jamil, Muhammad; Siddiqui, Numair Ahmed; Usman, Muhammad; Wahid, Ali; Umar, Muhammad; Ahmed, Nisar; Haq, Izhar Ul; El‐Ghali, Mohamed A. K.; Imran, Qazi Sohail; Rahman, Abdul Hadi Abd; Zhang, Shiqi
Abstract : Deep‐water massive sandstones (DWMS) are characterized by large volumes of sand accumulations which are considered as potential reservoir intervals in deep‐marine environments. Lithological variations and bed thickness statistics are used to interpret the distribution of massive sandstones in a deep‐marine fan‐lobe system. These massive sandstones are interpreted based on lithological heterogeneities and detailed facies analysis in seventeen exposed sections of the Late Palaeogene deposits in Sabah, NW Borneo. Sedimentary logs containing details of lithology textures and structures were used to recognize nine sedimentary facies of DWMS. These lithofacies were then grouped into three sedimentary facies associations: (1) massive facies association with basal part of turbiditic Bouma sequence, (2) massive facies association having soft‐sediment deformation structures, and (3) massive facies association with erosional features. The facies analysis portrays inner to middle submarine fan deposition and was later applied to reconstruct the distribution of a channel‐lobe complex. Individual sandstone bed thicknesses vary from 1 m to more than 8 m and the number of massive sandstones in submarine lobes range from less than 10% to more than 50%. The thicknesses of massive sandstones in channels are more than 8 m, whereas distal lobes have thicknesses from 1–2 m only. These sandstones are concentrated in channels, proximal and medial lobe settings that can also be verified from calculating the average of all maximum thickness of massive sand intervals that is, 8.91 m. The lithological heterogeneities and the processes associated with the deposition of these massive sandstones are vital for potential hydrocarbon reservoirs in the deep‐marine environments around the globe. Abstract : A generalized conceptual model for the distribution of DWMS facies 1–9 of submarine channel‐lobe complex in a deep‐marine sedimentary environment. (a–c) are the examples of DWMS facies with respective sedimentary logs.